The application of flipped classroom approach in online ESL/EFL teaching context (Eurasian Research Bulletin, 2022)
The theory and practice of blended learning is a topical issue of Uzbek and foreign linguodidactics. However, the application of the flipped learning model in teaching English as a foreign language and a second language have not yet been sufficiently studied. The article considers the inverted learning model as a tool for the internalization of students in the transition to an autonomous discourse in the target language. Multimodel resources and a scaffolding strategy are presented as a means of providing an individual learning trajectory and context-driven aspectual English learning. Various interactive forms of organizing educational material and means of developing its reflective understanding are designated as a mechanism for increasing the effectiveness of the formation of foreign language communicative competence